2016
DOI: 10.1111/1744-9987.12392
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Transplant Lymphoproliferative Disorder in Kidney Transplant Recipients: A Single‐Center Experience in Japan

Abstract: Post-transplant lymphoproliferative disorder is a serious complication of solid organ transplantation; however, few large studies have been performed in Asian institutions. We review our single-center experience with post-transplant lymphoproliferative disorder patients in Japan. We retrospectively evaluated patients with post-transplant lymphoproliferative disorder following kidney transplantation between January 1985 and December 2013. The patients were divided into early-onset post-transplant lymphoprolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, the optimal management of patients with PTLD is yet to be determined. Moreover, the associations of PTLD with patient and graft survival, 3,[24][25][26] return to chronic dialysis, 12,20,[24][25][26][27][28] and death with graft function 5,7,9,20 vary widely between existing studies and depend on factors such as the severity of PTLD, recipient age, and posttransplant monitoring of patients. 24 In order to provide additional insights into the incidence, risk factors, clinical management, and outcomes of PTLD in kidney recipients, we undertook a longitudinal, observational cohort study from Toronto General Hospital (TGH), the largest kidney transplant center in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal management of patients with PTLD is yet to be determined. Moreover, the associations of PTLD with patient and graft survival, 3,[24][25][26] return to chronic dialysis, 12,20,[24][25][26][27][28] and death with graft function 5,7,9,20 vary widely between existing studies and depend on factors such as the severity of PTLD, recipient age, and posttransplant monitoring of patients. 24 In order to provide additional insights into the incidence, risk factors, clinical management, and outcomes of PTLD in kidney recipients, we undertook a longitudinal, observational cohort study from Toronto General Hospital (TGH), the largest kidney transplant center in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that PTLD is one of the most common cancers in kidney transplant recipients. Moreover, presence of PTLD can reduce the patient and allograft survival [ 2 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the subjects in most of these studies were from a heterogeneous group involving both adult and pediatric patients and recipients of different types of solid organ. Furthermore, only very few studies of kidney transplant recipients with PTLD were recruited from the Asian population, especially the Chinese patients and these data are usually restricted to small case series [ 8 , 17 - 19 ]. The difference in EBV seropositivity and HLA frequencies between the Western and Asian population might influence the incidence, pattern and treatment outcome of PTLD in different geographical areas [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%